2019
DOI: 10.26493/2335-4194.12.121-132
|View full text |Cite
|
Sign up to set email alerts
|

Dark Events of the Istrian Countryside: An Electronic Media Perspective

Abstract: This pilot research illuminates the connection and reflection of past traumatic events in contemporary dark events. The purpose of the research is to provide a basic understanding of what dark events and dark tourism mean in a specific regional environment-the countryside of the trans-border region of Istria. Consequently, the media-constructed social reality related to dark events was identified with the help of a quantitative content analysis; cross tabulation and descriptive analyses were employed to resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…In order to analyse the contribution made by dark events to SDG16 in the Western Balkans, this exploratory research provided an SDA of media reports of these events, sampled from across the region. A corpus of media reports on thirty sport and commemorative events was developed in order to develop a novel analysis, extending the scope of dark events research beyond commemorations (Kennell et al, 2018;Laing & Frost, 2016;Suligoj, 2019) to include sport events which, in particular in this region, share dark characteristics linked to memory, politics and violence (Bairner, 2008;Brentin & Tregoures, 2016;Healy, 1991;Vejnovi c, 2014). This research shows that dark events of different types in the Western Balkans are part of a complex and seemingly permanent social system of cause-and-effect relationships, where excesses of verbal/physical violence often occur, including attacks on politicians, fans and property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to analyse the contribution made by dark events to SDG16 in the Western Balkans, this exploratory research provided an SDA of media reports of these events, sampled from across the region. A corpus of media reports on thirty sport and commemorative events was developed in order to develop a novel analysis, extending the scope of dark events research beyond commemorations (Kennell et al, 2018;Laing & Frost, 2016;Suligoj, 2019) to include sport events which, in particular in this region, share dark characteristics linked to memory, politics and violence (Bairner, 2008;Brentin & Tregoures, 2016;Healy, 1991;Vejnovi c, 2014). This research shows that dark events of different types in the Western Balkans are part of a complex and seemingly permanent social system of cause-and-effect relationships, where excesses of verbal/physical violence often occur, including attacks on politicians, fans and property.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have used the term "dark events" to refer to commemorative events that are associated with death, disaster and suffering (Kennell et al, 2018;Laing & Frost, 2016;Suligoj, 2019). Within leisure studies, the word dark has been associated with practices that involve deviance from social norms, or to denote associations with illegal or controversial subcultures (Blackshaw, 2018;Spracklen & Spracklen, 2012).…”
Section: Dark Commemorative Events In Post-conflict Areasmentioning
confidence: 99%
“…In the cluster of studies targeting the marketing aspects of dark tourism, the biggest challenge identified is the promotion of dark tourism. Recent studies have highlighted how electronic media and social media may have become useful resources in the promotion of dark tourism (Wight, 2020;Price & Kerr, 2017;Šuligoj, 2019;Tzanelli & Korstanje, 2016). A few studies also focus on the role played by cinema and web series in promoting dark tourism (Zerva, 2021).…”
Section: Knowledge Clusters Using Bibliographic Coupling (Rq3)mentioning
confidence: 99%
“…Museums' position as exclusive institutions are moving towards being more accessible and dialogic (Kim, 2018). Besides the possibility to arrange a multi-voices communication, media support the popularization of dark tourism destinations (Suligoj, 2019). Social media are also appropriate for crowdsourcing initiatives, as well as to spread letters and petitions.…”
Section: Stakeholders In the Heritage Contextmentioning
confidence: 99%